Understanding aesthetics of interaction: A repertory grid study - Mõttus, Mati; Lamas, David Ribeiro; Karapanos, Evangelos; Cockton, Gilbert (My University, 2016)
This work in progress paper explores users' perceptions of the aesthetics of interaction. We describe a qualitative study using the Repertory Grid Technique (RGT) that elicited individuals' personal constructs, bipolar adjectives such as beautiful vs ugly that characterize individuals' idiosyncratic ways of classifying and differentiating between a set of stimuli. The constructs were sorted by similarity, resulting in a set of aesthetic categories. Quantitative data (i.e., participants' ratings) from the RGT further enables us to assess the internal consistency of the emerging categories as well as to chart the design space of aesthetic interactions. All in all, 23 categories of aesthetics of interaction were established based on users' perceptions. These categories partially corroborated (e.g., speed, proximity, complexity) but also expanded (e.g., natural realism, congruence, dimensionality) prior work on experience qualities in Human-Computer Interaction (HCI).
Keywords: Aesthetics Of Interaction; Repertory Grid; Aesthetic Constructs